2002
DOI: 10.1051/parasite/2002092187
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of airport malaria : four cases in France during summer 1999

Abstract: These cases were geographically very close to each other and clustered in a short period of time during the summer of 1999. The phenotype and genotype of the Plasmodium falciparum isolates obtained from these patients were determined in order to know whether a single mosquito could have infected more than one subject. The genomic characterisation of isolates was performed using the polymorphic markers merozoite surface protein 1 (Mspl) and merozoite surface protein2 (Msp2) genes, the K and ɷ repeats domains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…On average, there are a few such infections each year among people who live near airports but have never traveled to an area of malaria endemicity. Among these, occasionally more than one infection occurs in a given place at one time, and analyses in France have confirmed that a pair of cases in 1994 and a cluster of four cases in 1999 each resulted from single P. falciparum genotypes (51,95). It is most likely that these clusters result from single mosquitoes infecting multiple people, as occurs frequently in areas of endemicity (40), although the possibility of secondary transmission locally (and thus the theoretical possibility of an outbreak) should be excluded only after careful consideration …”
Section: Outbreaks Epidemics and Reintroductions Of Malariamentioning
confidence: 99%
“…On average, there are a few such infections each year among people who live near airports but have never traveled to an area of malaria endemicity. Among these, occasionally more than one infection occurs in a given place at one time, and analyses in France have confirmed that a pair of cases in 1994 and a cluster of four cases in 1999 each resulted from single P. falciparum genotypes (51,95). It is most likely that these clusters result from single mosquitoes infecting multiple people, as occurs frequently in areas of endemicity (40), although the possibility of secondary transmission locally (and thus the theoretical possibility of an outbreak) should be excluded only after careful consideration …”
Section: Outbreaks Epidemics and Reintroductions Of Malariamentioning
confidence: 99%
“…This finding could suggest several infections caused by the same mosquito taking an interrupted blood meal. Although rare, such event had been previously reported in 1999 with three malaria cases induced [ 20 ]. Bites by distinct anopheline females coming from the same malaria focus and infected by the same clone cannot be totally excluded.…”
Section: Discussionmentioning
confidence: 98%
“…DNA was extracted with chelex-100 resin as previously reported [ 20 ]. Merozoite surface protein-2 (msp-2), which has been shown to be sufficiently discriminating in African parasite populations [ 21 ], was amplified by PCR for paired pre-treatment and failure samples to distinguish recrudescences from reinfections, as previously described [ 22 ]. Genotyping results PCR-adjusted were classified into three categories: 1) true recrudescences, 2) reinfections, and 3) mixed results (recrudescence and reinfection).…”
Section: Methodsmentioning
confidence: 99%